Poderes instrutórios do juiz no processo de conhecimento - Xavier, Trícia Navarro (2008)
Evidence law constitutes a procedural institute of great relevance, since it is designated to demonstrate the judge about the procedural truth which will serve as a basis for his sureness. Considering that the contemporary procedural law has been developing in order to give process the task of not only applying the material rights, but also applying the constitutional axiological load, the role of the judge in this intent has been very important, since it has been given to him – the judge – powers until then non-existent on procedural law – since this procedural law was always destined to solve private relations –, to give an answer to what doctrine has been calling “procedural publicization”. The probational field has been through great impact because of this paradigm change, and the judge, when it concerns to gather the proofs, started to have an active role when confronted to the eventual obstacles in the search of the truth. It is this probative initiative that will be subject to analysis, in its main meanings, with a different view of the contemporary position of the Brazilian doctrine. The main goal is to make jurists start to understand the judge’s finding of facts power in another way, in order to heat up the debates over the subject. The methodology applied, as a scientific method, was the deductive-dialectic one and, as an approach method, the descriptive historicexploratory of a quantum-qualitative bibliographical-documental method (context analysis). The research was developed basically by means of theoretical and literary revision argumentation, of national and foreign written works, since, as it was already mentioned, in the Brazilian judiciary system, when it concerns to the evidence field, it is constituted by the junction of the civil and common law systems. The results gathered were, by means of a critical analysis of the doctrine about the subject, the establishment of new solutions to the most intriguing questions. The conclusion of the studies was to demystify the limits imposed nowadays to the judge’s active role and to demonstrate that his finding of facts powers are very wide and many times decisive to an adequate jurisdictional use, in the new constitutional forms.